2021
DOI: 10.1016/j.bbrep.2021.100956
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular crowding effects on the kinetics of opposing reactions catalyzed by alcohol dehydrogenase

Abstract: In order to better understand how the complex, densely packed, heterogeneous milieu of a cell influences enzyme kinetics, we exposed opposing reactions catalyzed by yeast alcohol dehydrogenase (YADH) to both synthetic and protein crowders ranging from 10 to 550 kDa. The results reveal that the effects from macromolecular crowding depend on the direction of the reaction. The presence of the synthetic polymers, Ficoll and dextran, decrease V max and K m for ethanol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 119 publications
2
6
0
Order By: Relevance
“…This is consistent with previous findings for other enzymes individually encapsulated within VLPs that have shown high loading densities can lead to reduced activity (Fiedler et al, 2010;Minten et al, 2011). The decrease in enzyme activity as a result of apparent molecular crowding may be attributed to factors such as conformational changes and excluded volume effects (Norris and Malys, 2011;Wilcox et al, 2021). On the other hand, for alcohol dehydrogenase (AdhD) encapsulated at different densities in P22 VLPs, an increase in enzymatic activity was observed with an increase in AdhD loading (Sharma and Douglas, 2020).…”
Section: The Impact Of Tuning the Stoichiometry Of Co-encapsulated En...supporting
confidence: 91%
“…This is consistent with previous findings for other enzymes individually encapsulated within VLPs that have shown high loading densities can lead to reduced activity (Fiedler et al, 2010;Minten et al, 2011). The decrease in enzyme activity as a result of apparent molecular crowding may be attributed to factors such as conformational changes and excluded volume effects (Norris and Malys, 2011;Wilcox et al, 2021). On the other hand, for alcohol dehydrogenase (AdhD) encapsulated at different densities in P22 VLPs, an increase in enzymatic activity was observed with an increase in AdhD loading (Sharma and Douglas, 2020).…”
Section: The Impact Of Tuning the Stoichiometry Of Co-encapsulated En...supporting
confidence: 91%
“…6,14 The decrease in enzyme activity as a result of apparent molecular crowding may be attributed to factors such as conformational changes and excluded volume effects. 42,43 On the other hand, for alcohol dehydrogenase (AdhD) encapsulated at different densities in P22 VLPs, an increase in enzymatic activity was observed with an increase in AdhD loading. 5 However, wild-type SP induced macromolecular crowding in a concentration-dependent manner when coencapsulated with AdhD, suggesting that AdhD did not exhibit self-crowding but is affected by crowding in the presence of other proteins.…”
Section: Impact Of Tuning the Stoichiometry Of Co-encapsulated Enzyme...mentioning
confidence: 99%
“…As might be expected, cellular crowding affects diffusion rates, as well as protein aggregation and phase separation [ 74 ]. Many attempts to quantify these effects have used ‘inert’ crowding additives, such as dextran, ficol, or polythylene glycol [ 75 , 76 ]. Although such studies indicated the kinetic behaviour to be selectively affected, the nature of the crowding agent itself was found to be an important factor [ 74 , 77 ].…”
Section: Approximating the Activity Within The Cellmentioning
confidence: 99%